Family Tourist Characteristics in Parenting Health Education Model Approaches Bio Massage and CHSE Based at Kids Club Hotel Nusa Dua Bali - Nyoman Ribek; I Ketut Labir; Ni Luh Ketut Suardani; Wija Negara; Ni Made Dewi Ayu Virgayanti (Universitas Pendidikan Ganesha, 2022)
This research is motivated by the absence of a kids club hotel development module to reduce family tourists' worries about illness in children at tourist attractions, burdening families and parental burnouts and unfulfilled travel needs. The purpose of this research was to analyze the characteristics of family tourists, the level of anxiety, parental burnout, and the need for parenting health education, and to find a model design for parenting health education. The research method in phase 1 uses a quantitative descriptive research approach with a survey approach. The sampling strategy uses a purposive side technique with a sample size of 100 people during the survey and will be followed by the FGD method with 30 people. The results showed that the characteristics of family tourists were that most tourists were from foreign countries, especially Australia, enough worries, enough parental burnout, and health education parenting needs such as standards, achievement of quality and basic needs of children in health education parenting at kids club hotels were categorized as sufficient. It was concluded that foreign tourists need guidelines for the kids club model to reduce worries about falling ill at tourist attractions so that it becomes an attraction to increase the arrival of foreign family tourists.